2009
DOI: 10.1002/smll.200801378
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Activated Photoluminescence in Lead Selenide Colloidal Quantum Dots

Abstract: The thermal activation processes in PbSe colloidal quantum dots and their influence on the ground-state exciton emission are discussed. Activation of a dark exciton occurs at 1.4-7 K, assisted by an acoustic phonon coupling. Activation of a bright exciton occurs at 100-200 K, which appears as a sudden change in the photoluminescence band intensity, energy, and full width at half maximum. This activation overcomes the dark-bright-state splitting, when the activation temperature increases with the decrease of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
67
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 45 publications
17
67
2
Order By: Relevance
“…From a single exponential fit to the decay curves of a 4.6 nm PbSe QD sample (see Figure 4a), we obtain an experimental lifetime 0 of 0.969 Ϯ 0.002 s, 0.979 Ϯ 0.002 s, and 1.067 Ϯ 0.002 s respectively at a wavelength of 1375, 1425, and 1500 nm. These results agree with the 1.04 s measured by Kigel et al 15 for 4.7…”
supporting
confidence: 93%
“…From a single exponential fit to the decay curves of a 4.6 nm PbSe QD sample (see Figure 4a), we obtain an experimental lifetime 0 of 0.969 Ϯ 0.002 s, 0.979 Ϯ 0.002 s, and 1.067 Ϯ 0.002 s respectively at a wavelength of 1375, 1425, and 1500 nm. These results agree with the 1.04 s measured by Kigel et al 15 for 4.7…”
supporting
confidence: 93%
“…The cw-PL spectra of the smallest PbSe cores CQDs are dominated by a single exciton band over the entire temperature range, similar to the observation found in Ref. [21]. However, the emission spectra of the larger PbSe cores occasionally exhibit a split band at elevated temperatures.…”
supporting
confidence: 84%
“…39 However, the trend is interrupted in two distinct points: (i) occurrence of unusual climax in the intensity profile at a temperature between 150 K to 250 K, appearing at higher temperature in c/sh and c/a-sh, compared with that of the primary cores, but with a very small effect in a-c/a-sh CQDs. This abnormal climax was previously explained 21 as a thermal activation between dark and bright states, with activation energy (E a ) close to the LO phonon energy (LO (PbSe) = 16.8 meV, LO (PbS) = 26 meV). The values of E a of the investigated samples are listed in Table 3, spanning a range that is in close agreement to the suggested theoretical values of the dark-bright splitting in pure PbSe cores; 27 (ii) unexplained a minor decrease of the intensity <10 K with an activation energy ~ 0.4 meV, way below the acoustic phonon energy (LA, TA ~ 4-6 meV).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Inorganic core/shell heterostructures were formed either by epitaxial coating a semiconductor core by another semiconductor shell (e.g., CdSe/CdS and PbSe/PbS CQDs) or by a cation-exchange process, involving diffusion of foreign cations from the outer to the inner CQD layers (e.g., PbSe/CdSe and PbS/CdS CQDs) [29][30][31][32][33][34]. Our studies demonstrated the advantage of PbSe/PbSe x S 1−x [29,[35][36][37][38][39][40][41][42] and CdTe/CdTe x Se 1−x [43,44] alloyed heterostructures, where the alloyed interface reduced the crystallographic and dielectric mismatch between the core and the shell and also created a smooth boundary potential, which suppressed the Auger non-radiative relaxation processes in the CQDs.…”
Section: Introductionmentioning
confidence: 75%